HEDONISME YANG TERCERMIN DALAM FILM THE GREAT GATSBY - Thalib, Vidyawati Puteri; Sigarlaki, Stephani J.; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTThis research entitled â€œHedonism as reflected in a film The Great Gatsbyâ€ is a research that mainly focused on the analysis of hedonism lifestyle; aspects and properties in the film namely. This research emphasize the theory from Well & Tiger the AIO to search the form of aspects of hedonism in the film meanwhile the theory mise en scÃ©ne to search the used of properties in the film, by the end, the results shows two findings, they are; First, from Well & Tiger interest include The Jazz Age and the flapper, activities include Wall Street illegal businesses, and opinions include the characterization of the characters. Secondly as the results of properties from the theory of mise en scÃ©ne there are; alcohol, Rolls Royce, and branded fashion that pictured the hedonism style itself.Keywords: The aspects of hedonism, The Jazz Age, Hedonism lifestyle.